2013
DOI: 10.1200/jco.2013.31.15_suppl.11052
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of BIM deletion polymorphism in non-small cell lung cancer with epidermal growth factor receptor mutation.

Abstract: 11052 Background: Germ line alterations in the proapoptotic protein BCL2-like 11 (BIM) can have a crucial role in how a tumor responds to treatment. To clarify the clinical usefulness of detecting BIM deletion polymorphism in non-small cell lung cancer (NSCLC) with positive epidermal growth factor receptor (EGFR) mutation we examined the prognosis in patients with or without the BIM changes. Methods: Seventy NSCLC patients with positive EGFR mutation treated with EGFR-tyrosine kinase inhibitor (EGFR-TKI) betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 0 publications
2
19
2
Order By: Relevance
“…[33][34][35] On the basis of these results, studies have highlighted the clinical benefits of BH3-mimetic drugs or histone deacetylase inhibitors in patients with the BIM deletion polymorphism. 19,32 However, the BIM deletion polymorphism was not predictive of EGFR TKIs outcome in this study, which is consistent with previous findings in Korea from Lee et al 31 Data from Lee et al 31 demonstrated no difference in the PFS among patients with and without the BIM deletion polymorphism (11.9 months with BIM deletion vs. 11.3 months without, p = 0.791). Similarly, Isobe et al 32 reported that patients with the BIM deletion polymorphism had similar ORR and DCR but shorter PFS than did patients without the mutation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…[33][34][35] On the basis of these results, studies have highlighted the clinical benefits of BH3-mimetic drugs or histone deacetylase inhibitors in patients with the BIM deletion polymorphism. 19,32 However, the BIM deletion polymorphism was not predictive of EGFR TKIs outcome in this study, which is consistent with previous findings in Korea from Lee et al 31 Data from Lee et al 31 demonstrated no difference in the PFS among patients with and without the BIM deletion polymorphism (11.9 months with BIM deletion vs. 11.3 months without, p = 0.791). Similarly, Isobe et al 32 reported that patients with the BIM deletion polymorphism had similar ORR and DCR but shorter PFS than did patients without the mutation.…”
Section: Discussionsupporting
confidence: 90%
“…These proportions are relatively consistent with prior reports. 20,[31][32][33] We also found that the distribution of BIM deletion polymorphisms was not associated with any specific clinicopathologic features.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The inability of EGFRi to induce apoptosis has been recently delineated as an important mechanism of upfront resistance to EGFRi (9)(10)(11)(12)(48)(49)(50). Although these studies, including ours, have focused on a clearly important role for the proapoptotic BIM, MCL-1 has become an increasingly relevant drug target and accordingly the development of MCL-1-specific inhibitors has excelled (39,43,51).…”
Section: Discussionmentioning
confidence: 97%
“…BIM upregulation is essential for the induction of apoptosis in lung cancer cells with EGFR mutations treated with first‐generation EGFR‐TKI, and low BIM protein levels are associated with resistance to EGFR‐TKI . Underlying the importance of BIM in EGFR‐TKI resistance, a functional BIM deletion polymorphism, specifically, a 2903‐bp deletion in intron 2, was discovered in East Asian individuals (13%‐18%) and found to confer inferior responses to EGFR‐TKI . Subsequently, the BIM deletion was also found in South American patients with NSCLC (15.7%) .…”
Section: Introductionmentioning
confidence: 99%